Quantum Simulation of Entanglement Dynamics in a Quantum Processor - Retamal-Abarzua, J; Roman-Asenjo, P; Albarran-Arriagada, F (Institute of Physics, 2024)
We implement a five-qubit protocol in IBM quantum processors to study entanglement dynamics in a two qubit system in the presence of a simulated environment. Specifically, two qubits represent the main system, while another two qubits serve as the environment. Additionally, we employ an auxiliary qubit to estimate the quantum entanglement. Specifically, we observe the sudden death and sudden birth of entanglement for different inital conditions that were simultaneously implemented on the IBM 127-qubit quantum processor ibm _brisbane. We obtain the quantum entanglement evolution of the main system qubits and the environment qubits averaging over N = 10 independent experiments in the same quantum device. Our experimental data shows the entanglement and disentanglement signatures in system and enviroment qubits, where the noisy nature of current quantum processors produce a shift on times signaling sudden death or sudden birth of entanglement. This work takes relevance showing the usefulness of current noisy quantum devices to test fundamental concepts in quantum information. © 2024 IOP Publishing Ltd.